Estimation of packet time belay in high-speed computer networks - Махмуд Малик, Абу-А'ра; Балашов, А. Ю. (Proceedings of National Aviation University (archive), 1998)
Considered is one of the stages of analysis of high-speed computer networks - estimation of time delay of data transmission. Transmission medium is used as the routing network. Given and substained is the stochastic model of estimation of time delay in the data transmission network which is compared to relative model, allows take into account more fully the interaction of information flows. The received analytical dependencies can be used for increasing the efficiency of load control in computer networks